Atypical lymphangioma and hyperkeratosis in a patient with morbid obesity, - Cristian Morán-Mariños; Wendy Nieto-Gutierrez; Josmel Pacheco-Mendoza (Sociedade Brasileira de Dermatologia, 2020)
Abstract Lymphangioma is a rare and understudied pathology that is usually detected in the first decade of life, and its appearance in adults is rare. This report details a 51-year-old man with morbid obesity who presented, for the last eight months, multiple asymmetric tumor lesions with extension to the scrotal region. The diagnosis of circumscribed lymphangioma with associated infection was confirmed. This case report demonstrates an unusual presentation of the characteristics of the lymphangioma that are seldom described in the literature.